Alteration of the oral environment in patients undergoing esophagectomy during the perioperative period - Masami Yoshioka; Daisuke Hinode; Yota Yamamoto; Yoshihito Furukita; Akira Tangoku (University of São Paulo, 2013)
Objective: During the perioperative period, oral ingestion is changed considerably in esophagectomy patients. The aim of this study was to investigate oral environment modifications in patients undergoing esophageal cancer treatments due to changes in dietary intake and swallowing functions. Material and Methods: Thirty patients who underwent operation for removal of esophageal cancer in Tokushima University Hospital were enrolled in this study. Results: It was found that 1) the flow rate of resting saliva decreased significantly at postoperative period by deprived feeding for one week, although it did not recover several days after oral ingestion began, 2) the accumulation of dental plaque and the number of mutans streptococci in saliva decreased significantly after operation, while both increased relatively quick when oral ingestion began, and 3) the swallowing function decreased significantly in the postoperative period. Conclusions: These results suggest that dental professionals should emphasize the importance of oral health care and provide instructions on plaque control to patients during the perioperative period of esophageal cancer treatment.